Relationship between Molecular Subtype, Degree of Differentiation, and Lymph Node Metastasis with Survival of Breast Cancer Patients at Dr. M. Djamil General Hospital, Padang, Indonesia - Isra Analdo Arza; Daan Khambri; Rony Rustam; Hera Novianti; Husna Yetti (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Breast cancer has the highest incidence of all cancers in women worldwide. A molecular subtype of breast cancer, degree of differentiation, and lymph node metastasis are prognostic and predictive factors of breast cancer. This study aims to explore the relationship between molecular subtype, degree of differentiation, and lymph node metastasis with overall survival and disease-free survival of breast cancer patients at Dr. M. Djamil General Hospital Padang. Methods: This study was an analytic observational study with a retrospective cohort approach using secondary data from 68 subjects. The test variables in this study were the molecular subtype of breast cancer, the degree of differentiation, and lymph node metastasis which were obtained from secondary data and medical records. Another test variable is patient survival, namely overall survival (OS) and disease-free survival (DFS). Data analysis with the help of SPSS software in univariate, bivariate, and multivariate. Results: Patients with lymph node metastases were 7.94 times more likely to experience an event (death) (HR=7.94 95% CI: 0.91–78.2). Patients with lymph node metastases were 10.2 times more likely to experience an event (recurrence) (HR=10.2 95% CI: 1.03–101.1). Conclusion: Lymph node metastases are the factors most related to survival (overall survival and disease-free survival) of breast cancer patients at Dr. M. Djamil General Hospital, Padang, Indonesia.